UPAYA MENINGKATKAN HASIL BELAJAR FISIKA SISWA DENGAN MENGGUNAKAN METODE DISKUSI - Aminah Harahap; Fahma Yusmita (Gravity Journal, 2023)
The problem in this study is the low student physics learning outcomes due to the lack of precise learning methods used, as well as the low student learning scores on the subject of measurement. This research is a class action research (CAR) which aims to obtain data on student learning outcomes in measurement learning. PTK is carried out in 3 cycles and each cycle consists of 4 stages, namely planning, implementing, observing and reflecting. This research was conducted at SMA Negeri 1 Batangtoru. The subjects in this study were 39 class X-1 students and the object of this study was the use of discussion learning methods to improve students' physics learning outcomes. In collecting data, the techniques used were tests, observations, and interviews. The research results obtained were the average results of the first cycle test obtained an average of 62.92 and 48.71% completeness. Then the researcher continued to cycle II and the results showed that the results of the test cycle II averaged 73.71 and completeness was 69.23%, there had been an increase from cycle I, which was an average of 4.59 and completeness had increased by 10.25%. Furthermore, in cycle III the results obtained an average of 81.15 and increased from cycle II of 7.44 and completeness obtained results of 80.05% and increased from cycle II of 12.82%. Observation results, for teacher management in the learning process in cycle I obtained a score of 47.5% in cycle II obtained a percentage of 61.25% and in cycle III obtained a percentage of 83.75%. Results of observations of student activity during the teaching and learning process using the Discussion learning method in cycle I obtained a percentage of 48.25%, in cycle II student activity during the teaching and learning process obtained a percentage of 63.25% and in cycle III student activity during the teaching and learning process obtained a percentage of 85.75%. Based on the resultsof the study it can be concluded that the discussion learning method in Class X-1 of SMA Negeri 1 Batangtoru on the subject of Measurement can improve students' physics learning outcomes.